Measurement of charm production at central rapidity in proton-proton collisions at □s = 2.76 TeV - Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agocs, A. G.; Agostinelli, A.; Salazar, S. Aguilar; Ahammed, Z.; Masoodi, A. Ahmad; Ahmad, N.; et al. (SPRINGER, 2012)
The p(t)-differential production cross sections of the prompt (B feed-down subtracted) charmed mesons D-0, D+, and D*(+) in the rapidity range vertical bar y vertical bar K-pi(+), D+ -> K-pi(+)pi(+), D*(+) -> D-0 pi(+), and their charge conjugates, and was performed on a L-int = 1.1 nb(-1) event sample collected in 2011 with a minimum-bias trigger. The total charm production cross section at root s = 2.76 TeV and our previous measurements at root s = 7 TeV. The results were compared to existing measurements and to perturbative-QCD calculations. The fraction of c(d)over-bar D mesons produced in a vector state was also determined.
Keywords: Hadron-Hadron Scattering; HEAVY; HADROPRODUCTION; QUARKS; PP; Physics